Inter- and intra-annual patterns of Ulva prolifera green tides in the Yellow Sea during 2007–2009, their origin and relationship to the expansion of coastal seaweed aquaculture in China - Keesing, J.; Liu, D.; Fearns, Peter; Garcia, R. (Pergamon, 2011)
The large green-tide events that occurred in the Yellow Sea in 2008 (3489 km2) and 2009 (4994 km2) are shown to be novel events preceded only once by a much smaller event in 2007 (82 km2). The blooms originated in the coastal area of Jiangsu province and spread north-east towards the Shandong Peninsula. The blooms grew at different rates and mesoscale variability in surface winds explained the differences in the spatial and temporal patterns of blooms in 2008 and 2009. The 2009 bloom was tracked to its origin immediately offshore of extensive intertidal flats between Yancheng and Nantong where recent rapid expansion of Porphyra aquaculture has occurred. We review published hypotheses which have been advanced to explain the occurrence of blooms and in light of our findings, we conclude that the accumulation and disposal of waste Ulva prolifera from Porphyra aquaculture rafts is the most likely cause of the blooms.